Pediatric voice : a modern, collaborative approach to care - Kelchner, Lisa N.; Brehm, Susan Baker; Weinrich, Barbara Derickson (Plural Publishing, 2014)
Most speech-language pathologists see children as part of their practice. Pediatric Voice: A Modern, Collaborative Approach to Care offers a comprehensive and current review of the care of children with voice disorders. It includes an overview of anatomy and physiology of the pediatric laryngeal mechanism, associated neural controls, and phonatory behavior across childhood. A thorough discussion of the etiologic correlates of pediatric voice disorders is provided. The spectrum of evaluation techniques ranging from basic to innovative high tech instrumentation is presented. Evidence-driv.